Relative torque profiles of elite male youth footballers: Effects of age and pubertal development - Forbes, H.; Bullers, A.; Lovell, A.; McNaughton, L. R.; Polman, R. C.; Siegler, J. C. (International Journal of Sports Medicine, 2009)
This study aimed to establish the effect of age and pubertal development on relative peak torque in youth footballers. One hundred and fifty-seven subjects were arranged into U12-U18 age groups; of these 133 also completed a self-reporting measure of pubertal development (PDS) and were grouped accordingly. Bilateral isokinetic testing included mean peak torque/body weight (PT/BW) and angle of peak torque (AoPT) for reps 2-4 of 5 in concentric quadriceps (CQ), concentric hamstrings (CH) and eccentric hamstrings (EH) at 60°s-1. Two minutes rest were provided between concentric and eccentric tests for both legs. A significant increase with age was noted for PT/BW in CQ, CH and EH (P<0.05), although post hoc analyses revealed different patterns of significance dependent upon muscle and type of contraction. Specifically, the U18 s (CQ:2.20 nm/kg, CH:1.39 nm/kg, EH:2.16 nm/kg) were not significantly stronger than the U16 s and U15 s (CQ:2.42/2.29 nm/kg, CH:1.41/1.27 nm/kg, EH:2.22/2.15 nm/kg) even though they had entered full time training. The relationship between EH PT/BW and AoPT showed a weak but significant inverse correlation (P<0.001; R=-0.390 and -0.346 for dominant and non dominant legs). The findings of this study present unique football specific normative and age/PDS group data for PT/BW and AoPT, and the corresponding relationship between these variables.